Hearing Cultures: Essays on Sound, Listening and Modernity - Erlmann, Veit (New York Wenner-Gren Foundation for Anthropological Research London Berg, 2004)
Hearing Cultures is a timely examination of the elusive, often evocative, and sometimes cacophonous auditory sense. It answers such intriguing questions as: Did people in Shakespeare's time hear differently from us? In what way does technology affect our ears? Why do people in Egypt increasingly listen to taped religious sermons? Why did Enlightenment doctors believe that music was an essential cure? What happens acoustically in cross-cultural first encounters? The ear, as much as the eye, nose, mouth and hand, defines experience. This book shows how sound offers a refreshing new lens through which to examine culture and complex social issues.